THE OLDEST PEDIATRIC INSTITUTION IN RUSSIA - V.Yu. Albitsky; I.V. Viniarskaya ("Paediatrician" Publishers LLC, 2006)
The article outlines the principal historical periods of the oldest pediatric institution in Russia - since it was established as Moscow founding hospital to present days. The authors claims that the Scientific Center Of Children's Health of Russian academy of medical sciences has become a proximate successor to Moscow founding hospital. Key words: Moscow founding hospital, baby care hospital, Sciеntific Institute of Maternity and Infancy Care, Scientific and Research Pediatric Institute.